Experiencia profesional en gestión de la comunicación corporativa y marketing de servicios en el rubro educación y entretenimiento - Luna Borja, Rosario Lourdes (2020)
Service institutions, whether entertainment or educational, have always sought to achieve a leading position in the market and total satisfaction of the end customer. In the latter case, students increasingly demand greater willingness, timeliness, speed and effectiveness in the services required. Today, a strategic ally for educational institutions are the information technologies and virtual platforms that have served largely for their adaptation of portfolio and services to the trends and needs of the current context, so in the field of education, to the traditional courses of hard skills have been added programs aimed at entrepreneurship, women's management development and digital marketing among others as development of soft skills so important in the organizational culture of an institution. My experience in the service sector in the area of education and training, from the positions of marketing assistant, customer service manager, program coordinator and current entrepreneur allows me to analyze cases that are presented at different levels and obtain valuable information for continuous improvement by providing a unique customer experience at each stage of the process of acquiring the service, which will keep current customers and attract potential customers.